Chelation dependent selective adsorption of metal ions by Schiff Base modified SBA-15 from aqueous solutions. Issue 5 (October 2020) - Parambadath, Surendran; Mathew, Aneesh; Mohan, Anandhu; Ha, Chang-Sik
Graphical abstract: Highlights: Heterogeneous Schiff base adsorbents were derived from 2 hydroxybenzaldehyde (2-HB) and 4-hydroxybenzaldehyde (4-HB). The selective adsorption of metal ions from aqueous mixtures has been evaluated under identical pH conditions. 2-HB-SBA-15 exhibited 100% molar selectivity for Pb(II) ion at pH 2 and the selectivity turned to Cu(II) at higher pH. 4-HB-SBA-15 exhibited 54% selectivity for Pb(II) at pH 2 and a distributed selectivity for all ions at higher pH. Abstract: Mesoporous silica SBA-15 was modified with Schiff bases of 2-hydroxybenzaldehyde (2-HB) or 4-hydroxybenzaldehyde (4-HB), after silanization with (3-aminopropyl)triethoxysilane (3-APTES). The obtained heterogeneous Schiff bases (2-HB-SBA-15 and 4-HB-SBA-15) were analysed using sophisticated characterization techniques to disclose their successful formation and physico-chemical properties. Whether chelation plays any key role in the selective adsorption of metal ions was evaluated using aqueous mixtures containing Mn(II), Co(II), Ni(II), Cu(II), Cr(III), Zn(II), Pb(II) and Cd(II) ions in the pH range 2−6. Both materials exhibited different affinity towards metal ions from the same mixture under various pH conditions. 2-HB-SBA-15 exhibited 100 % selectivity towards Pb(II) ion at pH 2 while the selectivity turned to Cu(II) at higher pH. 4-HB-SBA-15, however, showed an affinity towards Cr(III) and Pb(II) at pH 2 while a distributed selectivity was observed with major portion to Cr(III), Pb(II) and Cu(II) at higher pH conditions. The observed affinity towards a particular metal ion was enhanced when considering the Cr(III), Pb(II) and Cu(II) ions in single and double concentrations in the mixture at pH 5. When analyzing the structure of both organic molecules, 2-HB-SBA-15 has a chelation possibility but 4-HB-SBA-15 has less. The difference in molar adsorption selectivities of the two organically modified mesoporous materials, 2-HB-SBA-15 and 4-HB-SBA-15 clearly indicates the effect of chelation in ligand over selective adsorption of metal ions from aqueous mixtures at identical adsorption conditions.